2004
DOI: 10.1046/j.0905-6157.2003.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of allergic rhinitis but not asthma among children in Hong Kong from 1995 to 2001 (Phase 3 International Study of Asthma and Allergies in Childhood)

Abstract: There is a worldwide belief that the prevalence of asthma and other allergic diseases is increasing but the measures used in many studies are susceptible to systematic errors. We examined the trend of asthma, allergic rhinitis and eczema prevalence in school children aged 6-7 years in Hong Kong from 1995 to 2001 using standardized ISAAC methodology. There were 4448 and 3618 children participating in 2001 and 1995, respectively. The prevalence of life-time rhinitis (42.4% vs. 38.9%, p < 0.01), current rhinitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
4
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 23 publications
(23 reference statements)
7
105
4
3
Order By: Relevance
“…12 According to many research projects applying the phase III ISAAC protocol, the prevalence of allergic rhinitis has been increasing in some countries. [2][3][4][5] In Brazil the mean prevalence of rhinitis was 16.8%. 13 No changes were detected in Porto Alegre, Salvador or São Paulo, but increases were observed in Curitiba and Recife.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 According to many research projects applying the phase III ISAAC protocol, the prevalence of allergic rhinitis has been increasing in some countries. [2][3][4][5] In Brazil the mean prevalence of rhinitis was 16.8%. 13 No changes were detected in Porto Alegre, Salvador or São Paulo, but increases were observed in Curitiba and Recife.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5] Allergic rhinitis, with its intimate association with asthma, is a public health problem in many countries, leading to the need for continuous monitoring of its tendencies.…”
Section: Introductionmentioning
confidence: 99%
“…En estudios no colaborativos, la mayor prevalencia en la población pediátrica está descrita por Wright y cols, siendo ésta de 42% a los 6 años de vida 25 . Es conocido el aumento en la prevalencia de rinitis en los últimos años, lo que podría estar determinado por la industrialización y los cambios en el estilo de vida: mayor polución ambiental, mejoría de las condiciones habitacionales, mejoría de la higiene, cambios en los hábitos dietarios [11][12][13][14][15]29,30 . Von Mutius y cols describieron una prevalencia de fiebre de heno de 8,6% en niños de 9 a 11 años residentes en Alemania Occidental, en comparación con una cifra de 3,4% en los residentes en Alemania Oriental en su estudio realizado entre 1989 y 1992 14 .…”
Section: N V E S T I G a C I ó Nunclassified
“…Often, it is found that rhinitis prevalence increases faster than asthma prevalence, which was also found to decrease in some countries (904,947,948,1896,(1917)(1918)(1919)(1920)(1921)(1922). It appears that in regions of highest prevalence, the proportion of subjects suffering from asthma or rhinitis may be reaching a plateau (1919).…”
Section: Epidemiologic Links Between Rhinitis and Asthmamentioning
confidence: 99%